A high - precision measurement chain for reference purposes. (December 2021) - Schaefer, André
Abstract: Reference transducers not only for high pressure (GPa) but also for high force (MN) and high torque (MN▪m) have been based on foil-type strain gauges for decades, due to their excellent signal-to-noise ratio and established, well-proven technology. Thus, reference transducers based on the principle of strain gauges are used for tracing back pressure higher than 100 … 200 MPa. This article shows how to further improve high-pressure precision measurement chains for up to 1.5 GPa, consisting of a reference transducer and a high-precision amplifier.